Explorations in the history of machines and mechanisms : proceedings of the fifth IFToMM Symposium on the History of Machines and Mechanisms /: proceedings of the fifth IFToMM Symposium on the History of Machines and Mechanisms. (2016) - Unknown
No abstract available